P04.12 The preclinical efficacy study using mesenchymal stem cells expressing TRAIL & CD for glioblastoma. (19th September 2018) - Ahn, S; Jeun, S
Abstract: Background: Our previous study using mesenchymal stem cells (MSCs) as delivery vehicles for tumor necrosis factor-related apoptosis inducing ligand (TRAIL) showed an anti-tumor effect in vitro and in vivo for glioblastoma. However, because most malignant glioma cells exhibit TRAIL resistance, we need to find new strategies to overcome it. We developed MSCs expressing both TRAIL and cytosine deaminase (CD) which convert the prodrug 5-fluorocytosine (5-FC) to the cytotoxic agent 5-fluorouracil (5-FU). We also immortalized these MSCs and introduced a doxycycline-dependent gene-inducible system to maintain the quality control. Lastly, we enhanced tumor tropism by overexpression of CCR2 and CXCR4. In this study, we investigated the anti-tumor efficacy of our novel MSCs (BM-03) with a 5-FC in vitro and in vivo orthotopic xenograft glioblastoma model. Material and Methods: Human bone marrow-derived MSCs were isolated and cultured as described previously after approval by our institutional review board. The multiple genes mentioned above were transfected into the MSCs using a lentivirus vector system. Using a U87 human glioma cell line and male athymic nude mice, we developed an orthotopic glioblastoma xenograft model. We injected BM-03 in a dose-dependent manner (control; low dose, 2.0X104 cells; intermediate dose, 1.0X105 cells, and high dose, 5.0X105 cells) intratumorally with the intraperitoneal injection of 5-FC (500 mg/kg). Additionally, with in vivo bioluminescence imaging, we assessed the tumor volume. Results: First, we confirmed the doxycycline-dependent inducible gene expression system of BM-03 and showed the high expression of TRAIL, CCR2, and CXCR4 using FACS analysis. The synergistic anti-tumor efficacy of BM-03 with 5-FC was shown compared with BM-03 alone, in vitro . Moreover, we revealed the enhanced tumor tropism of BM-03 using in vivo bioluminescence imaging. After BM-03 injection of the contralateral side of the tumor, we could see that our MSCs moved toward the inoculated tumor lesion located on the contralateral side. Finally, when treated with BM-03 and 5-FC, we showed an increased antitumor efficacy in terms of both the median survival rate (control, 44 days; low dose, 46 days; intermediate, 57 days, and high dose, 69 days) and the tumor volume in a dose-dependent manner compared with the control and BM-03 only in the orthotopic xenograft glioblastoma mouse model. Conclusion: Our novel immortalized and inducible MSCs expressing TRAIL and CD showed an enhanced antitumor efficacy in an orthotopic xenograft glioblastoma model. This successful preclinical result will serve as a foundation for IND approval and a phase I clinical trial using our novel MSCs (BM-03).